2017
DOI: 10.1186/s13063-017-2250-7
|View full text |Cite
|
Sign up to set email alerts
|

Rectally administered indomethacin to prevent post-ESWL-pancreatitis (RIPEP): study protocol for a randomized controlled trial

Abstract: BackgroundPancreatic extracorporeal shock wave lithotripsy (P-ESWL) is the first-line therapy for large pancreatic duct stones. Although it is a highly effective and safe procedure for the fragmentation of pancreatic stones, it is still not complication-free. Just like endoscopic retrograde cholangiopancreatography (ERCP), pancreatitis is the most common complication. To date, nonsteroidal anti-inflammatory drugs (NSAIDs) have proven to be the only effective prophylactic medication for post-ERCP pancreatitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Concerning pharmaco-prevention modalities, to date, non-steroidal anti-inflammatory drugs (NSAIDs) are the only medications to be effective in PEP prevention (Cote and Elmunzer, 2016 ; Chandrasekhara et al, 2017 ). Furthermore, evidence is emerging that rectal administration of NSAIDs such as indomethacin or diclofenac just before or after ERCP might reduce the risk and severity of post-procedure pancreatitis (Dumonceau et al, 2014 ; Qian et al, 2017 ). According to the updated European Society of Gastrointestinal Endoscopy (ESGE) guidelines for PEP prevention, there is no evidence that drugs such as corticosteroids, antioxidants, heparin, sphincter of Oddi pressure reducers, and/or anti-inflammatory drugs (other than indomethacin and diclofenac) can effectively reduce the risk of PEP (Dumonceau et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning pharmaco-prevention modalities, to date, non-steroidal anti-inflammatory drugs (NSAIDs) are the only medications to be effective in PEP prevention (Cote and Elmunzer, 2016 ; Chandrasekhara et al, 2017 ). Furthermore, evidence is emerging that rectal administration of NSAIDs such as indomethacin or diclofenac just before or after ERCP might reduce the risk and severity of post-procedure pancreatitis (Dumonceau et al, 2014 ; Qian et al, 2017 ). According to the updated European Society of Gastrointestinal Endoscopy (ESGE) guidelines for PEP prevention, there is no evidence that drugs such as corticosteroids, antioxidants, heparin, sphincter of Oddi pressure reducers, and/or anti-inflammatory drugs (other than indomethacin and diclofenac) can effectively reduce the risk of PEP (Dumonceau et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, the administration of non-steroidal anti-inflammatory drugs (NSAIDs) like indomethacin and diclofenac or hydration with lactated Ringer's solution (LR) or normal saline are recommended for preventing PEP. 8,[12][13][14][15][16][17] In a concluding systematic review and meta-analysis, Elmunzer et al showed a lower risk of PEP with the administration of diclofenac and indomethacin. 18 Additionally, pancreatic stent placement (PSP), was first introduced in the United States in the late 1990s, as a common clinical practice and extended as an effective preventing tool for PEP in high-risk cases.…”
mentioning
confidence: 99%